2010
DOI: 10.1002/mar.20339
|View full text |Cite
|
Sign up to set email alerts
|

From a commodity to an experience: The moderating role of thematic positioning on congruity‐based product judgment

Abstract: Research in positioning strategy suggests that a product schema, when presented in a moderately incongruent fashion, can evoke a greater degree of positive evaluation than if presented congruently with consumer expectations. This phenomenon has been coined the schema congruity effect. To date, one of the limitations of the phenomenon is that it has been applied almost exclusively to taxonomic stimuli, with little reference to thematic, eventlike stimuli. Two experiments verified that taxonomic and thematic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…This work affords several important insights, particularly given the renewed interest in schema congruity theory over the last 5 years (Jhang et al 2012;Krishna, Elder, and Caldara 2010;Landwehr, Wentzel, and Hermann, 2013;Noseworthy, Finlay, and Islam 2010;Noseworthy and Trudel 2011;Roggeveen, Goodstein, and Grewal 2014). Where the results may have particular theoretical relevance is in reflecting on past work.…”
Section: Discussionmentioning
confidence: 88%
“…This work affords several important insights, particularly given the renewed interest in schema congruity theory over the last 5 years (Jhang et al 2012;Krishna, Elder, and Caldara 2010;Landwehr, Wentzel, and Hermann, 2013;Noseworthy, Finlay, and Islam 2010;Noseworthy and Trudel 2011;Roggeveen, Goodstein, and Grewal 2014). Where the results may have particular theoretical relevance is in reflecting on past work.…”
Section: Discussionmentioning
confidence: 88%
“…Crucially, these differences in perceived novelty and evaluation are hypothesized to occur when processing is unconstrained (i.e., not guided by the marketer). But often the marketer can manipulate the type of information that is available during evaluation, such as attributes shared by the brand and the extension product, and such communicative constraints affect evaluations (Aaker & Keller, 1990;Bridges et al, 2000;Kirmani & Shiv, 1998;Noseworthy et al, 2010). Study 3 therefore compared the perceived novelty and evaluation of taxonomic and thematic brand extensions under processing conditions that were either less constrained or more deliberative.…”
Section: Processing and Evaluation Of Taxonomic And Thematic Brand Exmentioning
confidence: 99%
“…For example, Campbell and Goodstein () showed that when perceived risk is high, a congruous product is preferred to a moderately incongruous product. In addition, Noseworthy, Finlay, and Islam () and Noseworthy and Trudel () indicated that when the product is thematically (vs. taxonomically) positioned or when the product is experientially (vs. functionally) positioned, a congruous product is preferred to a moderately incongruous product. However, in this study, the authors observed different inverted‐U evaluation patterns according to PNS.…”
Section: Discussionmentioning
confidence: 99%